Risk factors, risk stratification and risk-specific surveillance strategies after endovascular aneurysm repair: study protocol for a Delphi study by the International RIsk Stratification in EVAR (IRIS-EVAR) working group. Issue 4 (25th April 2022) - Antoniou, George A; Schermerhorn, Marc L; Forbes, Thomas L; Cheng, Vincent; Antoniou, Stavros A; Golledge, Jonathan; Verhagen, Hence J M; Torella, Francesco
Abstract : Introduction: Several risk factors for adverse events after endovascular aneurysm repair (EVAR) have been described, but there is no consensus on their comparative prognostic significance, use in risk stratification and application in determining postoperative surveillance. Methods and analysis: A scoping review of the literature was conducted to identify risk factors for adverse events after EVAR. Main adverse events were considered post-EVAR abdominal aortic aneurysm rupture and reintervention. Risk factors were grouped into four domains: (1) preoperative anatomy, (2) aortic device, (3) procedure performance and (4) postoperative surveillance. The Delphi methodology will be used to steer a group of experts in the field towards consensus organised into three tiers. In tier 1, participants will be asked to independently rate risk factors for adverse events after EVAR. In tier 2, the panel will be asked to independently rate a range of combinations of risk factors across the four domains derived from tier 1. A risk-stratification tool will then be built, which will include algorithms that map responses to signalling questions onto a proposed risk judgement for each domain. Domain-level judgements will in turn provide the basis for an overall risk judgement for the individual patient. In tier 3, risk factor-informed surveillance strategies will be developed. Each tier will typically include three rounds and rating will be conducted using a 4-point Likert scale, with an option for free-text responses. Ethics and dissemination: Research Ethics Committee and Health Research Authority approval has been waived, since this is a professional staff study and no duty of care lies with the National Health Service to any of the participants. The results will be presented at regional, national and international meetings and will be submitted for publication in peer-reviewed journals. The risk stratification tool and surveillance algorithms will be made publicly available for clinical use and validation.